Blue Swimming Crab’s Conservation Area Determination in The North of Java Sea Using Reproductive Indicator - Putri Novianingrum, Milka; Hartati, Retno; Pribadi, Rudhi; Käll, Sofia; Redjeki, Sri (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Despite being operated on a small scale, Blue Swimming Crab (BSC), Portunus pelagicus fishery substantially contributes to Indonesia's fisheries as the country's third-largest export commodity after tuna and shrimp. The high of BSC’s demand led to pressure on its stock. Hence a conservation area is needed to be set up, in this study, was proposed using reproduction indicators. with the case study of BSC Stock in Keboromo Waters, Pati Regency, North Central Java. The samples were collected from 38 sampling points at a distance of 2-12 miles from the coastline during November-December 2022 using collapsible crab traps.  A reproduction observation on female crabs was carried out on their carapace width and gonad maturity stage. The data then were analyzed for the percentage of egg-berried females (EBF), size at first maturity (Lm) and first captured (Lc), and their spawning potential Ratio (SPR).  This study found that the mature crabs (GMS2) in November and December were higher than in other stages while the proportion of ovigerous females (EBF) in December was higher than in November. At several sampling points, the size at first captures (Lc) was higher than that at first maturity (Lm) indicating a decrease in resource stocks due to a delay in the recruitment process. SPR of 19% showed that reproductive potential should be maintained before recruitment is limited, therefore based on the existence of EBF in particular sampling points it is recommended three conservation areas as a temporary no-take zone in BSC fishing ground in Keboromo Watres, Pati Regency.